Embarazo abdominal, a propósito de un caso. - ESPINOZA QUINTEROS, Jimmy; GOMERO, Raúl; GONZALES, Edgard; GONZALES, Isolda (Revista Médica Herediana, 2013)
We present a case of primary abdominal pregnancy that represented a diagnostic and therapeutic challenge because its inespecific clinical presentation. Knowledge of the differential diagnosis and the complications of abdominal pregnancy is required to avoid the mistakes that could be life threatening for the mother. A review of the literature is done, as well. (Rev. Med Hered 1997; 8: 78-82).